ANALISIS NIAT PERILAKU MELALUI PENGALAMAN WISATAWAN STUDI PADA TAMAN MINI INDONESIA INDAH JAKARTA - Nazwirman Nazwirman (ISOQUANT : Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
This research was conducted at Taman Mini Indonesia Indah (TMII). The variables used are perceived value, tourist experience and behavioral intention. The result is that perceived value has a direct effect on the tourist experience. The perceived value has a direct effect on behavioral intention. Tourist experience has direct effect on behavioral intention and the experience of tourists is able to mediate between perceived intention and behavioral intention. Research makes theoretical and managerial contributions. Providing value implications that play an important role in shaping and fostering positive tourist experiences by adding values that are emphasized on tourists so that it has an impact on their behavioral intentions. The value felt by tourists to visit TMII has quite an interesting experience, but most of them do not really want to visit unless invited to family, relatives and friends. Research Objectives provide insights into their construction and influence and develop a scale of measurement of perceived value and explore different dimensions of tourists in shaping tourist experiences and build theoretical frameworks to explain the relationships between variables